Modification of the existing maximum residue levels for acetamiprid in honey and various oilseed crops. (24th August 2022) - ,; Bellisai, Giulia; Bernasconi, Giovanni; Brancato, Alba; Cabrera, Luis Carrasco; Castellan, Irene; Ferreira, Lucien; Giner, German; Greco, Luna; Jarrah, Samira; Leuschner, Renata; Magrans, Jose Oriol; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Nufarm Europe Gmbh submitted a request to the competent national authority in Austria to modify the existing maximum residue levels (MRLs) for the active substance acetamiprid in honey, linseeds, poppy seeds, mustard seeds and gold of pleasure seeds. The data submitted in support of the request were found to be sufficient to derive MRL proposals for linseeds, poppy seeds, mustard seeds and gold of pleasure seeds. For honey, however, data gaps were identified by EFSA and were not fully addressed by the justification provided by the applicant. Considering the remaining uncertainties, risk managers are given the option to either accept the justification provided and the related uncertainties or to merge the provided data with a data set from a previous application to derive an MRL proposal. Adequate analytical methods for enforcement are available to control the residues of acetamiprid in plant matrices and in honey at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of acetamiprid according to the reported agricultural practices is unlikely to present a risk to consumer health.